Occurrence of acid erosion of the teeth, actinomycosis and polioencephalomalacia in flock of sheep fed wet low pectin citrus pulp - Vinícius José Moreira Nogueira (Arquivos do Instituto Biológico, 2018)
ABSTRACT: The citrus pulp can be used as a substitute in ruminant feed reducing costs and maintaining the nutritional quality of food. However, this compound should be used carefully so as not to cause harm to the animals. The present report aims to describe the occurrence of dental erosion, actinomycosis and polioencephalomalacia in sheep raised and kept with a wet low pectin citrus pulp based diet, composing 50% of roughage. Actinomycosis was diagnosed in five animals through clinical and radiographic examinations and microbiological culture, and, after treatment, three animals were cured. Polioencephalomalacia was confirmed in ten animals by clinical diagnostics, in nine out of ten animals by therapeutic diagnosis, and in one animal by post-mortem anatomopathological examination. According to the observed, we recommend caution when large amounts of citrus pulp are used as bulky food.